PELAKSANAAN KEGIATAN EKSTRAKURIKULER KEAGAMAAN DI MAN KOTA PALANGKARAYA SECARA DARING - Supiani, Supiani; Muryati, Dewi; Saefulloh, Ahmad (FKIP, Universitas Palangka Raya, 2020)
The impact that Covid 19 has on teaching and learning activities is quite pronounced, this can be seen from learning that should be done directly and meaningfully now can only be done independently. That way students do indirect learning by utilizing online or online learning that is deemed quite effective in situations like today. Extracurricular activities are activities carried out in developing certain aspects of what is found in the ongoing curriculum, including those related to how the actual application of knowledge learned by students is in accordance with the demands of their life needs and the surrounding environment. Extracurricular is an educational activity outside of class hours which is shown to help the development of students, according to their needs, potentials, talents, and interests through activities that are specifically organized by students and / or educational staff who are capable and authorized at school.